Utilizing Coconut Shell Waste Into A Crafts and Driving Economic Income in The COVID Pandemic in Berangir Plantation Village - Inggi Priyanata; Bayu Eko Broto; Nurintan Asyiah Siregar (PT Mattawang Mediatama Solution, 2022)
Coconut shells have the characteristics to be used as various handicraft products. Study this aim for knowing benefit waste shell coconut Becomes something craft hand and push income economy during the Covid pandemic. Study this set Berangir Plantation Village as location research. The method used in this research is the method of observation and experiment. Thus, coconut shell waste can become more economically valuable and of course, will have an effect on increasing people's income. The result of this research is a craft product that has aesthetic value and is beneficial to the community and can be of economic value.